Forced Disappearances, Indigenous Peoples and Socio-Environmental Conflict in Mexico - Quintana-Navarrete, Miguel (Victims & offenders, 2024)
Criminological research on forced disappearances is scarce despite the prevalence and seriousness of these phenomena and criminology’s growing interest in mass atrocities. By focusing on forced disappearances in Mexico, we argue that the exploitation of the natural resources of indigenous peoples through extractivism and other ecologically harmful enterprises, and these groups’ resistance to such exploitation, generates social conflict and the violent targeting of indigenous activists, resulting in increased disappearances. Consistent with this argument, we find that the proportion of the indigenous population is positively associated with the forced disappearance rate and the presence of conflicts stemming from extractive projects.